The Role of Public Relations in Managing the State-Owned Enterprise Reputation Crisis: A Conceptual Study of the Case of PT Pertamina (Persero) - Putri, Cindy Varelia; Anggraeny, Monicca; Chasanah, Siti Nur; Subrata, Pramudya Ibnu (The Indonesian Institute of Science and Technology Research, 2026)
This study examines the conceptual role of Public Relations (PR) in managing organizational reputation and public trust, with a particular focus on State-Owned Enterprises (SOEs) in the digital era. Rapid developments in information technology have increased the risk of reputational crises, requiring organizations to adopt transparent and responsive communication strategies. Using a conceptual paper approach and a structured literature review, this research synthesizes various theoretical frameworks, including Situational Crisis Communication Theory and the organization-public relationship model. The analysis indicates that PR functions as a strategic managerial pillar that builds